2023
DOI: 10.25225/jvb.23046
|View full text |Cite
|
Sign up to set email alerts
|

Rank-dependency of major urinary protein excretion in two house mouse subspecies

Miloš Macholán,
Kristina Daniszová,
Petra Hamplová
et al.

Abstract: Chemical communication is important for many social mammals. Scent-related gene clusters have undergone extraordinary expansion in some species, such as the house mouse (Mus musculus). One such family encodes major urinary proteins (MUPs). MUPs can provide recipients with complex information about the signaller and potentially serve as honest signals of social rank. In this study, we examined the development of overall MUP production in two mouse subspecies in the context of establishing their social hierarchy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 92 publications
(165 reference statements)
0
1
0
Order By: Relevance
“…Second, the expression of individual MUPs is regulated by a complex endocrine system involving testosterone, thyroxine, and growth hormone [83,84]. Consequently, can be down-regulated or up-regulated depending on health, food supply, age, and other conditions [85,86], or as a consequence of social interactions [87], although the latter potential influence might have been prevented or at least reduced by individual housing of the mice under study. It has been suggested that uMUPs are able to provide individual identity information in urine markings (e.g., [36,50,53,[88][89][90][91][92]).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the expression of individual MUPs is regulated by a complex endocrine system involving testosterone, thyroxine, and growth hormone [83,84]. Consequently, can be down-regulated or up-regulated depending on health, food supply, age, and other conditions [85,86], or as a consequence of social interactions [87], although the latter potential influence might have been prevented or at least reduced by individual housing of the mice under study. It has been suggested that uMUPs are able to provide individual identity information in urine markings (e.g., [36,50,53,[88][89][90][91][92]).…”
Section: Discussionmentioning
confidence: 99%